Homologous series of low molecular weight (C1-C10) monocarboxylic acids, benzoic acid and hydroxyacids in fine-mode (PM2.5) aerosols over the Bay of Bengal: Influence of heterogeneity in air masses and formation pathways. (October 2017) - Boreddy, Suresh K.R.; Mochizuki, Tomoki; Kawamura, Kimitaka; Bikkina, Srinivas; Sarin, M.M.
Abstract: Low molecular weight monocarboxylic acids (LMW monoacids) are most abundant volatile organic compounds (VOCs) in the atmosphere and often act as important contributors to the acidity of precipitation in addition to inorganic acids. However, there is a large uncertainty in the sources and secondary formations of these acids in the atmosphere. This study reports homologous series of LMW monoacids, including normal (C1 -C10 ), branched chain (iC4 -iC6 ), aromatic (benzoic acid) and hydroxyacids (lactic and glycolic acids) in the fine-mode (PM2.5 ) aerosols collected over the Bay of Bengal (BoB) during a winter cruise (December 2008 to January 2009). The samples were associated with two distinct continental air masses arriving from the Indo-Gangetic Plain (IGP-outflow) and Southeast Asia (SEA-outflow). The molecular distributions of organic acids are characterized by the dominance of formic acid (C1 ) followed by acetic acid (C2 ) and nonanoic acid (C9 ) in the IGP-outflow, whereas dominance of C1 or C9 was observed in the SEA-outflow followed by C2 . Formic-to-acetic acid (C1 /C2 ) ratios were higher than unity (mean: 1.3 ± 0.3) in the IGP-outflow, whereas they were less than unity (0.9 ± 0.5) in the SEA-outflow. These results suggest that secondary formation of organic acids is largely important in the IGP-outflow whereas primary emission is a major source of organic acids in the SEA-outflow. Based on the correlation coefficient matrix analysis and C1 /C2 and C4 /C3 ratios, we consider that the sources of C1 are probably associated with the secondary formation via the oxidation of biogenic VOCs, while C2 has both primary and secondary formations associated with anthropogenic sources in the IGP-outflow. On the other hand, C1 and C2 have similar sources (both primary and secondary) originated from biomass burning and bacterial activities via long-range atmospheric transport in the SEA-outflow, as inferred from the MODIS fire spot data, significant concentrations of isovaleric acid (iC5 ), and a significant correlation (r = 0.67) between nss-K + and total LMW monoacids. Graphical abstract: Highlights: We determine the homologous series of low molecular weight monoacids over BoB. The marine boundary layer over BoB was influenced the IGP- and SEA-outflow. Formic-to-acetic acid ratios (C1 /C2 ) were larger than unity in the IGP-outflow. Propionic and isovaleric acids (C3 and iC5 ) were higher in the SEA-outflow. Hydroxyacids (lactic and glycolic) were higher in the IGP-outflow.